A review of length-weight relationships of freshwater fishes in Malaysia - Amonodin, Mohamad Radhi; Mohd Fadzil, Nurul Fazlinda; Mohammad Noor Azmai, Amal; Hashim, Rohasliney (De Gruyter Open, 2018)

(untitled)
This manuscript reviews the length-weight relationships (LWRs) of freshwater fishes in Malaysia. A total of 102 LWRs of fishes gathered from literature pertaining to 64 freshwater fish species were analysed. A meta-analysis from 13 previous reports showed that the b values was ranged from 2.19 (Clarias batrachus) to 4.106 (Barbodes binotatus). Out of 64 observed species, 47 species (11 families) experienced positive allometric growth, while another 23 species (eight families) and 31 species (12 families) were recorded under isometric and negative allometric growth, respectively. The fish LWRs observed can be used as an indicator of environmental changes and fish ecological health for freshwater fishes in Malaysia.